Prevalence of salmonella Infections in Patients Attending St. Dominic Hospital, (Akwatia)-Eastern Region - Dakorah, Mavis Puopelle (2014)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirement for the award of Master of Science degree, January-2014